2011
DOI: 10.1111/j.1442-2042.2011.02729.x
|View full text |Cite
|
Sign up to set email alerts
|

Length of site‐specific positive surgical margins as a risk factor for biochemical recurrence following radical prostatectomy

Abstract: Objectives: Positive surgical margins (PSM) have been associated with biochemical recurrence (BCR) after radical prostatectomy, but the significance of PSM length and location are debated. We assessed the impact of PSM lengths at specific locations for BCR in an open radical prostatectomy series. Methods: Detailed clinical and pathological data were collected from 117 post-prostatectomy patients with PSM from 1984 to 2004 at our institution. PSM locations were classified as apex, mid-gland , base, bladder neck… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
32
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(34 citation statements)
references
References 35 publications
2
32
0
Order By: Relevance
“…A multivariable Cox model will not level out these differences and will be unable to render these prognosticators of BCR comparable. In the study by Hsu et al ., apical PSM was not independently significant as compared with other localisations, and multifocal PSM was significantly related to reduced BCR (57%; HR = 0.43, P = 0.002) as compared with solitary PSM in univariate analysis 1 . In accordance with the aforementioned illustrated findings, our results did not show significant differences in BCR rate of apical versus non‐apical PSM in univariate analysis; however, we did note a significant difference in BCR of apical PSM versus absent PSM 2 .…”
mentioning
confidence: 76%
See 3 more Smart Citations
“…A multivariable Cox model will not level out these differences and will be unable to render these prognosticators of BCR comparable. In the study by Hsu et al ., apical PSM was not independently significant as compared with other localisations, and multifocal PSM was significantly related to reduced BCR (57%; HR = 0.43, P = 0.002) as compared with solitary PSM in univariate analysis 1 . In accordance with the aforementioned illustrated findings, our results did not show significant differences in BCR rate of apical versus non‐apical PSM in univariate analysis; however, we did note a significant difference in BCR of apical PSM versus absent PSM 2 .…”
mentioning
confidence: 76%
“…Hsu et al . refer their main message of a high impact of anterior PSM to 15 patients (7 with solitary anterior PSM) assessed within 21 years at Stanford University Medical Center 1 . In contrast, our series does not contain patients with anterior PSM.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…The authors reported the prognostic significance of surgical margin status in 117 prostate specimens derived from open radical retropubic prostatectomy 1 …”
mentioning
confidence: 99%